2023
DOI: 10.20944/preprints202310.0803.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lumbar Spine Coronal Balance Parameters as a Predictor of the Rehabilitation Management Outcomes in Patients With Radiculopathy Due to Lumbar Disc Herniation: A Multicenter Prospective Cohort Study

Yaser AH Aljallad,
Ibrahim M. Moustafa,
Mohamed Badr
et al.

Abstract: A multicenter, prospective cohort study conducted in 5 physiotherapy clinics in the UAE from January 2021 to March 2023 to assess coronal lumbar spine radiographic parameters as a predictor of conservative therapy outcomes in patients suffering from low back and leg pain due to lumbar disc herniation (HNP). Ninety patients (mean age 44 yrs., 54% male) with lumbar HNP underwent conservative therapy. All participants received lumbar spine MRI and radiography to assess spine alignment. Interventions included spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The results of the study by Aljallad et al in 2023 study showed that in patients with chronic lower back pain and radiculopathy caused by lumbar disc herniation, the likelihood of success of six-month outcomes was significantly influenced by younger age, less education, and better coronal radiographic lumbar spine alignment [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
“…The results of the study by Aljallad et al in 2023 study showed that in patients with chronic lower back pain and radiculopathy caused by lumbar disc herniation, the likelihood of success of six-month outcomes was significantly influenced by younger age, less education, and better coronal radiographic lumbar spine alignment [ 34 ].…”
Section: Reviewmentioning
confidence: 99%